The association between the angiotensin converter enzyme (ACE), AT1R and AT2R receptor gene polymorphisms and breast cancer: a case control study - Castro, Andrés Felipe; Loango, Nelsy; Ruíz, Bayron; Landázuri, Patricia (Revista Colombiana de Obstetricia y Ginecología, 2011)
Introduction: breast cancer is the second most common type of cancer and the fifth cause of death due to cancer around the world. The components of the renin-angiotensin system are potential candidates for chemoprevention therapy: the angiotensin converter enzyme (ACE) and type 1 and 2 angiotensin II receptors (AT1R and AT2R). Objective: establishing an association between ACE gene polymorphisms, AT1R and AT2R receptors and breast cancer. Materials and methods: 50 cases and 50 controls were included and their genetic polymorphisms genotyped. Results: genotype II occurred with greater frequency in controls than in the cases whilst the ID genotype had greater frequency in the cases (without having statistically significant differences). No type of additive effect of genotypes was found with the risk of breast cancer in the population being studied. Conclusions: susceptibility to breast cancer has been described as being a complex phenomenon in which many genes may play an important role. In the case of the population studied here, the polymorphisms evaluated were not associated with breast cancer. Further studies having greater methodological rigor regarding this topic are required before changes in clinical practice can be proposed.